Energization of Outflowing O+ by Double‐Pickup in Earthward Plasma Jets From Lobe Reconnection and in Magnetosheath Flow - H. Koike; M. Yamauchi; S. Taguchi; H. Nilsson; I. Dandouras (Geophysical Research Letters)
Abstract This study reports a case of energetic oxygen ions (O+) with energies around 20 keV, observed at the high‐latitude magnetopause during lobe reconnection. In the adjacent lobe/mantle region, another O+ beam, outflowing directly from the ionosphere, was observed with energies of approximately 1 keV. The energies and velocity distribution functions of O+ indicate that the observed 20 keV O+ are accelerated through double pickup processes. A test particle simulation shows that the outflowing O+ ions are first picked up by an earthward plasma jet from lobe reconnection and energized up to ∼3 keV. Subsequently, they are picked up by the tailward magnetosheath flow and further energized up to ∼15 keV. A strong gradient in the convection electric field at the magnetopause current layer, which tends to form during lobe reconnection, is likely to play an important role in the generation of energetic O+.